Management in Shaping Akhlakul Karimah According to the Qur'anic Concept - Yanto, Murni (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
Interpretation of Surah Al-Araf verse 179, Surah Al-Ahzab verse 21, and Surah Al-Baqarah verse 26 related to the management of noble morals in the Quran, reveals that these verses contain implicit meanings about morals in the modern era that are increasingly declining. This study is a library research conducted by collecting data through readings, books, and relevant literature. The results of the study: show that the management of noble morals is in line with Surah Al-Araf verse 179 which states that Hell is provided for jinns and humans who do not use reason, sight, and hearing that Allah has given in the best possible way; in Surah Al-Ahzab verse 21, the Prophet Muhammad (SAW) is described as a benchmark of life and an example for humanity with four characteristics: 1. Shidiq (truth), 2. Amanah (trustworthy), 3. Fathanah (wisdom), and 4. Tabligh (dissemination); Meanwhile, in the letter of Al-Baqarah verse 26, it is emphasized that obedience to Allah is the most important, because Allah will mislead those who do not want to believe and be pious, as an example of a mosquito that teaches that even small creatures obey Him. In contrast, humans gifted with reason, heart, and mind often do not want to believe and be pious, so they become wicked.